Using Chat Group Discussion on Whatsapp to Increase Students’ Vocabulary - Febria Zananda, Tiray (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2021)
Abstract Many people’s everyday lives points at new possibilities for conducting online and mobile focus groups. This paper offers new empirical insights from using the method as part of a digital ethnography with young activists. The presence of WhatsApp in participants’ everyday lives offers a context with high ecological validity. The paper suggests that this opens up new options for designing online focus groups. WhatsApp also offers opportunities for creating more inclusive group discussions also finds that this familiarity and inclusivity affords the potential for group deliberation, which can be particularly valuable in participatory research.